A discourse analysis of female political leaders’ speech styles / Jacqueline a/p Anthonysamy - Anthonysamy, Jacqueline (2014)
The change in women’s roles in recent times has certainly contributed to the change in female speech styles. Power and dominance which were once considered traits of the male gender are now superseded by power and dominance owned by the female gender. When female began their politic career four decades ago, it became a controversial sight as society and perceptions that failed to comply with the characteristic of the female gender opposed the idea of a female running the government. However, as years go by, the female gender has appeared strong on the political front and has gained not just recognition and acceptance from the society but also reputation for their unwavering contributions in the political world. This study examined the female political leaders’ speech styles and how selected linguistic strategies influenced the enactment of power and leadership among the society. The study analysed written speeches by noteworthy female political leaders from the past and also present using the Discourse Analysis approach. The speeches were analysed to examine the selected linguistic strategies employed by the female political leaders and how these strategies have influenced the enactment of power and leadership. The study concludes with summary of findings that reveal the use of selected linguistic strategies which have influenced the enactment of power and leadership through solidarity, common interest and emotional connection which acts to persuade audience hence strengthen their position as a leader.